Analysis of the Effectiveness of Pain Management with Benson Relaxation Technique and 0.9% NaCl Compress in DVT (Deep Vein Thrombosis) Patient : Analisis Efektivitas Manajemen Nyeri dengan Teknik Relaksasi Benson dan Kompres NaCl 0,9% pada Pasien DVT (Deep Vein Thrombosis) - Badrus Sholeh; Ruris Haristiani; Rondiantho; Sri Wahyuningsih (Caring : Jurnal Keperawatan, 2022)
Deep vein thrombosis (DVT) is a condition where a blood clot forms in the deep venous circulatory system. Generally, patients experience pain, swelling, increased visibility of skin veins, erythema, cyanosis, and fever. Benson relaxation technique and 0.9% NaCl compress is a combination of nursing interventions that can support the success of medical interventions to overcome changes in the pain scale. This scientific work aims to determine the effectiveness of nursing care in deep vein thrombosis patients with the application of Benson relaxation techniques and 0.9% NaCl compresses. Not through research ethics tests because interventions are commonly applied and only observations are made on the value of changes in the pain scale. Nursing care is given to Mr. C for 3 consecutive days with the application of the Benson relaxation technique and 0.9% NaCl compress. There was no decrease in pain scale on the first day with a pain scale of 6 (NRS). However, there was a decrease in the pain scale on the second and third days with pain scales of 4 and 2. Case analysis showed that Benson relaxation provides a sense of comfort and relaxation resulting in endorphins that affect pain impulses and 0.9% NaCl compresses provide skin stimulation thereby reducing pain transmission through C and delta A fibers are small in diameter, so that the synaptic gate closes the transmission of pain impulses. These results cannot be separated from the provision of other interventions. It is expected that nurses can optimally educate patients about the effectiveness of Benson's relaxation techniques and 0.9% NaCl compresses and carry out them according to standard operating procedures during treatment in hospitals and at home.   Deep vein Thrombosis (DVT) adalah suatu kondisi terbentuknya bekuan darah dalam sistem peredaran vena dalam. Umumnya pasien mengalami nyeri, bengkak peningkatan visibilitas vena kulit, eritema, sianosis,  dan demam. Teknik relaksasi benson dan kompres NaCl 0,9% adalah kombinasi intervensi keperawatan yang dapat menunjang keberhasilan intervensi medis untuk mengatasi perubahan pada skala nyeri. Karya ilmiah ini bertujuan untuk mengetahui efektivitas asuhan keperawatan pada pasien deep vein thrombosisi  dengan penerapan teknik relaksasi benson dan kompres NaCl 0,9%. Tidak melalui uji etik penelitian karena intervensi lazim diterapkan dan hanya dilakukan pengamatan terhadap nilai perubahan dari skala nyeri. Asuhan keperawatan diberikan pada Tn. C selama 3 hari berturut-turut dengan penerapana teknik relaksasi benson dan kompres NaCl 0,9%. Tidak terjadi penurunan skala nyeri pada hari pertama dengan skala nyeri 6 (NRS). Akan tetapi terjadi penurunan skala nyeri pada hari kedua dan ketiga dengan skala nyeri 4 dan 2. Analisa kasus menunjukkan relaksasi benson memberikan rasa nyaman dan rileks sehingga menghasilkan endorphine yang mempengaruhi impuls nyeri dan kompres NaCl 0,9% memberikan stimulasi kulit sehingga mengurangi transmisi nyeri melalui serat C dan delta A berdiameter kecil, sehingga gerbang sinaptik menutup transmisi impuls nyeri. Hasil ini tidak lepas dari pemberian intervensi lain. Diharapkan perawat secara optimal dapat melakukan edukasi kepada pasien tentang efektivitas teknik relaksasi benson dan kompres NaCl 0,9% serta menjalankannya sesuai standar operasional prosedur saat perawatan di rumah sakit maupun di rumah.